Peroral Endoscopic Myotomy for Pediatric Achalasia: A Retrospective Analysis of 21 Cases With a Minimum Follow-Up of 5 Years - Peng, Dongzi; Tan, Yuyong; Li, Chenjie; Lv, Liang; Zhu, Hongyi; Liang, Chengbai; Li, Rong; Liu, Deliang (Frontiers in Pediatrics, 2022)
Background: Peroral endoscopic myotomy (POEM) has shown promising short-term safety and efficacy in pediatric patients, while long-term outcomes are largely unknown. This study aimed to assess the clinical effects of POEM for pediatric achalasia who had a follow-up of at least five years. Methods: Pediatric patients from a single center who underwent a POEM between October 2011and November 2016 were respectively collected and analyzed for long-term clinical outcomes. Patients were contacted to evaluate current symptoms and encouraged repeat endoscopy and manometry. Clinical success, procedure-related parameters, adverse events, gastroesophageal reflux disease after POEM and quality of life were evaluated. Results: Twenty-four patients who underwent POEM in our center were studied, with a mean age of 14.42±2.65. Two of the 24 patients (8.3%) had previous treatment. The mean of the procedure time was 58.67±19.10 min, 8.3%(2/24) of patients experienced perioperative adverse events. The current symptom scores were obtained from twenty-one patients at a mean follow-up of 92.57 months, the remainder were lost to follow up after a mean of 38 months. Eckardt scores were significantly improved from preoperative baseline (preoperative 7.67±1.62 vs. current 0.86±1.28, P<0.001). Long-term overall success was achieved in 95.8% of patients and none required retreatment for symptoms. 12.5% of patients were suffered from clinical reflux. 76.2% of patients expressed satisfaction with POEM. No severe adverse events were observed during the operation and the 5-years follow-up. Conclusions: POEM resulted in successful symptomatic mitigation in a majority of pediatric patients after five years. A multi-center large-scale, prospective study is necessary for a confirmed conclusion.